The benefits of pulmonary rehabilitation in patients with COVID-19 - He, Zhen-feng (ERJ Open Res, 2021)
This editorial reviews the evidence supporting benefits of pulmonary rehabilitation in #COVID19 patients, as well as some unanswered research questions https://bit.ly/39JY3SU